Inhibitory Effect of Gallic Acid on 1 2 Dimethyl Hydrazine Induced Biochemical Alterations Colonic Bacterial Enzymes and Xenobiotic Metabolizing Enzymes in Rats - N Nalini, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Inhibitory Effect of Gallic Acid on 1 2 Dimethyl Hydrazine Induced Biochemical Alterations Colonic Bacterial Enzymes and Xenobiotic Metabolizing Enzymes in Rats